PENGGUNAAN TEPUNG LIMBAH LABU KUNING DALAM RANSUM TERHADAP PENAMPILAN PRODUKSI AYAM RAS PETELUR - Komalig, Devis F.; Leke, Jein Rinny; Laihat, J.; Sarajar, C. (Universitas Sam Ratulangi, 2016)
THE EFFECT OF PUMPKIN WASTE MEAL IN LAYING HEN FEED ON PERFORMANS PRODUCTION. This research was to find out the use of pumpkin waste meal on performance in the production of laying hens. The purpose of this research was to observe the effect of the use of pumpkin waste meal performance in the production of feed for laying hens. A total of 100 MB 402 laying hens from 42 week of age were randomly alloted to four dietary treatments with 5 replication groups of 4 hens. Dietary treatment were; basal diet (R0), basal diet 98% + 2% WCP (R1), basal diet 96% + 4% WCP (R2), basal diet 94% + 6% WCP (R3), basal diet 92% + 8% WCP (R4). The variable were the feed Consumption, hen day production, feed conversion. Data was analyzed with completely randomized Design ( CRD ). The addition of in the feed was not influenced significantly (P > 0,05) to the feed consumption, hen day production, feed conversion. Based on the research that is done it can be concluted that the use of waste carrot pumpkins in the feed at the level of 8% show no significantly different result on the feed consumption, hen day production, feed conversion. Keyword : Pumpkin waste meal, performance laying hens, performance of production